Genome-wide DNA methylation analysis of transient neonatal diabetes type 1 patients with mutations in ZFP57. Issue 1 (December 2016) - Bak, Mads; Boonen, Susanne; Dahl, Christina; Hahnemann, Johanne; Mackay, Deborah; Tümer, Zeynep; Grønskov, Karen; Temple, I.; Guldberg, Per; Tommerup, Niels
Abstract Background Transient neonatal diabetes mellitus 1 (TNDM1) is a rare imprinting disorder characterized by intrautering growth retardation and diabetes mellitus usually presenting within the first six weeks of life and resolves by the age of 18 months. However, patients have an increased risk of developing diabetes mellitus type 2 later in life. Transient neonatal diabetes mellitus 1 is caused by overexpression of the maternally imprinted genesPLAGL1 andHYMAI on chromosome 6q24. One of the mechanisms leading to overexpression of the locus is hypomethylation of the maternal allele ofPLAGL1 andHYMAI . A subset of patients with maternal hypomethylation atPLAGL1 have hypomethylation at additional imprinted loci throughout the genome, includingGRB10, ZIM2 (PEG3 ), MEST (PEG1 ), KCNQ1OT1 andNESPAS (GNAS-AS1 ). About half of the TNDM1 patients carry mutations inZFP57, a transcription factor involved in establishment and maintenance of methylation of imprinted loci. Our objective was to investigate whether additional regions are aberrantly methylated inZFP57 mutation carriers. Methods Genome-wide DNA methylation analysis was performed on four individuals with homozygous or compound heterozygousZFP57 mutations, three relatives with heterozygous ZFP57 mutations and five controls. Methylation status of selected regions showing aberrant methylation in the patients was verified using bisulfite-sequencing. Results We found large variability among the patients concerning the number and identity of the differentially methylated regions, but more than 60 regions were aberrantly methylated in two or more patients and a novel region withinPPP1R13L was found to be hypomethylated in all the patients. The hypomethylated regions in common between the patients are enriched for the ZFP57 DNA binding motif. Conclusions We have expanded the epimutational spectrum of TNDM1 associated withZFP57 mutations and found one novel region withinPPP1R13L which is hypomethylated in all TNDM1 patients included in this study. Functional studies of the locus might provide further insight into the etiology of the disease.